Physical-anthropogenic influence on house crow (Corvus splendens) abundance in urban areas with varying levels of urbanization - Wardah Mohd-Saleh,; Naim Mustafa,; Nor Halizam Ismail,; Farah Shafawati Mohd-Taib, (Penerbit Universiti Kebangsaan Malaysia, 2025)
House crow (Corvus splendens) is a well-known invasive species that has successfully been introduced outside of its native range and colonised many countries. Their population boom has caused nuisance to humans, especially those living in big cities. This study aimed to determine the influence of physical and anthropogenic factors towards the crow abundance, focusing on their night roosts. Ten selected roosting sites were grouped into highly and less urbanized sites, and several physical-anthropogenic variables were inspected. Crow census was conducted between 1730 and 1930 h, approaching roosting time. PCoA indicates a relatively strong effect of the physical-anthropogenic measures towards the crow abundance, with high urban intensity harbours greater crow abundance. GLMM analysis shows physical factors such as canopy cover and food sources positively influenced the crow abundance, whereas anthropogenic factors (disturbance index: pedestrian, traffic, trash, parked vehicle) negatively influenced the crow abundance (p<0.05). This suggests that crows were highly influenced by their physical surroundings, yet more adaptable to human presence. Controlling physical factors is essential for reducing suitable sites for crows to roost and breed. This study elucidates strategic plans to be undertaken by authorities and even the public to keep the crow population under control, to ensure a healthier environment for humans and other urban dwellers.